2011
DOI: 10.3390/s111211736
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Quantum Dots for Biomedicial Applications

Abstract: Semiconductor quantum dots (QDs) are nanometre-scale crystals, which have unique photophysical properties, such as size-dependent optical properties, high fluorescence quantum yields, and excellent stability against photobleaching. These properties enable QDs as the promising optical labels for the biological applications, such as multiplexed analysis of immunocomplexes or DNA hybridization processes, cell sorting and tracing, in vivo imaging and diagnostics in biomedicine. Meanwhile, QDs can be used as labels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(87 citation statements)
references
References 112 publications
0
83
0
4
Order By: Relevance
“…The choice to evaluate the liver, the spleen, and the kidney to monitor QD toxicity in vivo was made based on previous studies. 22,50,53,54 Our results showed that fluorescence emitted by CdS and …”
Section: In Vivo Studiesmentioning
confidence: 62%
See 2 more Smart Citations
“…The choice to evaluate the liver, the spleen, and the kidney to monitor QD toxicity in vivo was made based on previous studies. 22,50,53,54 Our results showed that fluorescence emitted by CdS and …”
Section: In Vivo Studiesmentioning
confidence: 62%
“…13,21 Nonetheless, besides the surface functionalization of the conjugated system, the overall cell behavior and the nanotoxicological response of the living organism are significantly governed by the nanoparticle size, surface characteristics such as hydrophobicity and charge, steric hindrance, chemical functional groups, and biochemical affinities at the biointerfaces. 5,22,23 Despite the great interest in understanding the nanotoxicity of QDs, 3 a systematic and comprehensive investigation comparing the cytotoxicity responses and the complex mechanisms comprising QD-based nanoconjugates made of Cd-based (toxic) and Zn-based (nontoxic) cores and surface functionalization by aminopolysaccharides was not found in the consulted literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescent dyes that have frequently been applied in TE studies are DNA stains (DAPI, Hoechst, propidium iodide, SYTO) [13,122], membrane stains (DiA, DiI, DiO, BODIPY) [38,123] or cytoplasmic stains such as calcein, CellTracker blue or CFDA [85,124,125], but also actin labelling with labelled phalloidin [61,85] as well as organelle markers (MitoTracker for mitochondria or LysoTracker for lysosomes) are widely being used [74]. An interesting approach is the use of fluorescent semiconductor nanocrystals (Qdots or Qtracker) with excellent optical and spectral properties [86]. Qtracker is taken up irrespective of the cell type, shows low cytotoxicity, remains inside the cells for extended time periods and is detectable even in very low concentrations.…”
Section: Imaging Of Labelled Structuresmentioning
confidence: 99%
“…Therefore, bright and photostable dyes (e.g. Alexa Fluor, Cy, MFP or Qdot series) are used in many TE studies [85][86][87][88]. CFM is used to stain both fixed and live cells with nuclear, cytoplasmic, membrane-bound dyes or-for protein-specific detectionantibody-coupled dyes [59,64,65,68,69,76] (immunohistochemistry: [39,89]).…”
Section: Transillumination and Fluorescence Microscopymentioning
confidence: 99%